Foresight-Driven Digital Transformation and Innovation Performance in Tourism MSMEs: A Capability Complementarity Perspective - Eman Sulaiman; Adi Santoso; Vigory Gloriman Manalu; Daduk Merdika Mansur; Hartanto Halim; Asep Kosasih (Bulletin of Network Engineer and Informatics, 2026)
Tourism micro, small, and medium enterprises (MSMEs) in West Java operate in increasingly dynamic environments shaped by digital platforms, shifting consumer behavior, and rising sustainability expectations. While digital transformation is often promoted as a strategic solution, many MSMEs struggle to translate digital adoption into meaningful innovation outcomes. This study develops and empirically tests a foresight-driven digital transformation framework that explains how strategic foresight capability, digital transformation capability, and green marketing orientation jointly influence innovation performance. Drawing on dynamic capabilities theory and sustainability-oriented marketing logic, this study employs a sequential mixed-method design. The qualitative phase identifies context-specific manifestations of foresight practices, digital transformation activities, and green marketing behaviors among tourism MSMEs. The quantitative phase, using PLS-SEM analysis of 214 MSMEs, examines the relationships among the constructs and the moderating effect. The results reveal that strategic foresight capability significantly enhances digital transformation capability and green marketing orientation, confirming its role as an upstream dynamic capability. Furthermore, digital transformation capability and green marketing orientation both positively influence innovation performance, with a stronger emphasis on marketing innovation. Importantly, the findings demonstrate a significant complementarity effect, where green marketing orientation strengthens the impact of digital transformation capability on innovation performance. This study contributes to the literature by positioning strategic foresight as a micro-foundation of digital transformation capability, and by integrating digital transformation and sustainability orientation into a unified framework. Practically, the findings highlight the importance for MSMEs to develop simple foresight routines, integrated digital capabilities, and credible sustainability-driven marketing strategies to enhance innovation outcomes.